Alcohol-Activated Vanadium-Containing Polyoxometalate Complexes in Homogeneous Glucose Oxidation Identified with 51V-NMR and EPR Spectroscopy - Wesinger, Stefanie; Mendt, Matthias; Albert, Jakob (ChemCatChem, 2021)
Alcoholic solvents, especially methanol, show an activating affect for heteropolyacids in homogenously catalysed glucose transformation reactions. In detail, they manipulate the polyoxometalate-based catalyst in a way that thermodynamically favoured total oxidation to CO2 can be completely supressed. This allows a nearly 100 % carbon efficiency in the transformation reaction of glucose to methyl formate in methanolic solution at mild reaction conditions of 90 °C and 20 bar oxygen pressure. By using powerful spectroscopic tools like 51V-NMR and continuous wave EPR we could unambiguously prove that the vanadate-methanol-complex[VO(OMe)3]n is responsible for the selectivity shift in methanolic solution compared to the aqueous reference system.
CRIS-Team Scopus Importer:2021-06-25
Keywords: EPR spectroscopy; Keggin polyoxometalates; NMR spectroscopy; solvent effect; vanadium redox chemistry